A Poet King. (2nd January 2022) - Rozman, Mateja
ABSTRACT : The following abridged and adapted newspaper article deals with the Slovenian Romantic poet France Prešeren who was supported by his friend the linguist, historian and literary critic Matija Čop. Prešeren proved that Slovenia was a nation because of its literature. According to the theory of the brothers Schlegel a nation exists only if its language can create high-brow poetry.